Penyuluhan Bahaya Narkoba, Gadget, dan Pergaulan Bebas Untuk Siswa SMA Negeri 1 Lhoknga - Lensoni; Mansura Feby Amanda; Futry Maysura; Erna Safitri; Noeroel Arham; Cut Rahmawati; Meliyana (Universitas Lancang Kuning, 2021)
Persuasive counseling can prevent drug use in students. Through counseling, students are expected to understand the dangers of drugs, gadgets, and promiscuity. The community service aims to provide counseling concerning the dangers of drugs, gadgets, and promiscuity for Year 12 students at SMAN 1 Lhoknga Class. To determine the success of the counseling, a pre-experimental design method, a One-Group posttest-posttest design, was used. The samples were 13 students selected through simple total sampling. The data were analyzed using a paired-sample t-test, with a significance level of 0.05. The results showed that most of the respondents' knowledge before counseling was in a low category (61%). After counseling, it was in the high category (92%). The bivariate analysis results showed the p-value of 0.00, indicating that there was an influence of the counseling on Year 12 students' knowledge about the dangers of drugs, gadgets, and promiscuity at SMAN 1 Loknga. This counseling positively impacts the future development of students to avoid drugs, gadgets, and promiscuity